Sleep quality, anxiety, and depression among perioperative caregivers of children with tethered cord syndrome: a cross-sectional survey analysis - Lin, Jinrun; Li, Hao; Xia, Suqin; Cheng, Qing; Lin, Dou; Fan, Dehong; Zhuo, Qing; Kang, Yulan (Frontiers in Pediatrics, 2025)
ObjectivesThis study aimed to investigate the relationship between sleep quality, anxiety, and depression among perioperative caregivers of children with tethered cord syndrome.MethodsA cross-sectional study design was employed to recruit primary caregivers of children undergoing surgery for tethered cord syndrome from Fujian Children's Hospital between February 2022 and December 2023. Participants were required to complete some questionnaires, including the Pittsburgh Sleep Quality Index (PSQI), the Self-Rating Anxiety Scale, and the Self-Rating Depression Scale. Statistical analyses like chi-square tests, t-tests, and logistic regression were carried out to evaluate the associations between sleep quality, anxiety, and depression.ResultsA total of 149 caregivers were included in the study and completed all the questionnaires. The findings indicated that the prevalence of sleep disorders among caregivers was 31.5%. Correlation analysis revealed a significant positive association between anxiety and depression. Multifactorial regression analysis identified younger age of the child, presence of comorbidities, extended duration in a prone position postoperatively, and prolonged caregiving time as independently significant factors contributing to sleep disorders in caregivers.ConclusionsThe study determined the occurrence of sleep disorders among primary caregivers of children with tethered cord syndrome. Furthermore, where the young age of the child, the presence of comorbidities, the time the child spent in a prone position after the operation, and the time spent caring for the child were significant factors. Future studies should explore the potential mechanisms and causal connections between caregiver sleep disorders and these crucial factors.